2000
DOI: 10.1177/00220345000790041301
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived Oral Health Status, Psychological Well-being, and Life Satisfaction in an Older Adult Population

Abstract: Numerous studies have demonstrated that many older adults have problems chewing, pain, difficulties in eating, and problems in social relationships because of oral disorders. However, it is not clear if these functional and psychosocial outcomes affect broader psychological well-being and life satisfaction. Consequently, this paper begins to address the question, 'Does poor oral health compromise the quality of life?'. Initial cross-sectional analyses used data derived from the seven-year follow-up of the Onta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
193
0
13

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(220 citation statements)
references
References 21 publications
11
193
0
13
Order By: Relevance
“…Investigações a respeito da autopercepção da qualidade de vida relacionada à saúde bucal têm sido desenvolvidas especialmente em paí-ses desenvolvidos como Estados Unidos 11,12,13 , Inglaterra 14 ; Austrália 15,16,17 e Canadá 18,19,20,21 . No Brasil, algumas investigações acerca do tema foram conduzidas, apesar disso existe ainda a necessidade de mais pesquisas para melhor compreensão dos fatores associados com a autopercepção da saúde bucal em nossa cultura 5,7,9,22,23,24,25,26,27,28,29,30,31,32 .…”
Section: Introductionunclassified
“…Investigações a respeito da autopercepção da qualidade de vida relacionada à saúde bucal têm sido desenvolvidas especialmente em paí-ses desenvolvidos como Estados Unidos 11,12,13 , Inglaterra 14 ; Austrália 15,16,17 e Canadá 18,19,20,21 . No Brasil, algumas investigações acerca do tema foram conduzidas, apesar disso existe ainda a necessidade de mais pesquisas para melhor compreensão dos fatores associados com a autopercepção da saúde bucal em nossa cultura 5,7,9,22,23,24,25,26,27,28,29,30,31,32 .…”
Section: Introductionunclassified
“…Locker et al 11 defined OHRQoL measurement instruments as those that assess the proportion of oral diseases and disorders, which in turn affect the function and assessment of psychosocial well-being. The differences between the questionnaires designed for this purpose relate to the number of questions, the question content, the answer format, the grouping of topics in different domains, and the number of domains.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 Aesthetics and functional aspects of conventional dentures also affect social behavior and self-confidence. 10 Locker et al 11 defined OHRQoL as "the extent to which oral disorders affect the functioning and psychosocial well-being. Currently, OHRQoL is considered an essential factor for assessment of the treatment success of implant-retained mandibular overdentures (IMO).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that positive self-evaluation in positive oral health is considered an important predictor of a better psychological well-being, self-esteem and life satisfaction over time [27][28][29]. Similarly, self-efficacy is considered an important key element of motivation for health changes, and studies indicated that the higher the perceived self-efficacy, that is, the individual's feeling on trusting his/her abilities to take the necessary actions to improve and maintain health, the greater the level of perseverance and persistence to performed certain behavior or activity [30].…”
Section: Discussionmentioning
confidence: 99%